Super-achromatic monolithic microprobe for ultrahigh-resolution endoscopic optical coherence tomography at 800 nm. Issue 1 (December 2017) - Yuan, Wu; Brown, Robert; Mitzner, Wayne; Yarmus, Lonny; Li, Xingde
Abstract Endoscopic optical coherence tomography (OCT) has emerged as a valuable tool for advancing our understanding of the histomorphology of various internal luminal organs and studying the pathogenesis of relevant diseases. To date, this technology affords limited resolving power for discerning subtle pathological changes associated with early diseases. In addition, it remains challenging to access small luminal organs or pass through narrow luminal sections without potentially causing trauma to tissue with a traditional OCT endoscope of a 1-1.5 mm diameter. Here we report an ultracompact (520 µm in outer diameter and 5 mm in rigid length) and super-achromatic microprobe made with a built-in monolithic fiber-optic ball lens, which achieves ultrahigh-resolution (1.7 µm axial resolution in tissue and 6 µm transverse resolution) for endoscopic OCT imaging at 800 nm. Its performance and translational potential are demonstrated by in vivo imaging of a mouse colon, a rat esophagus, and small airways in sheep. Optical coherence tomography is an established optical tool for in vivo clinical imaging and diagnosis applications, but endoscopic technologies remain limited. Here, Yuan et al. develop a flexible, narrow diameter, super-achromatic endoscopic probe for ultrahigh-resolution in vivo OCT imaging of small luminal organs or narrow constrictions.